Characterization of O-Carboxymethyl Chitosan – Gum Arabic Coacervates as a Function of Degree of Substitution. Issue 9 (1st September 2016) - Huang, Guo-Qing; Xiao, Jun-Xia; Jia, Lin; Yang, Jian
Abstract : Three O-carboxymethylated chitosans (O-CMCs) with degrees of substitution (DS) 0.41, 0.51, and 0.83 were synthesized and the effects of the DS of O-CMC on its coacervation with gum Arabic (GA) and partial characteristics of resultant coacervates were investigated. All the O-CMCs exhibited the same optimum pH of 3.0 for coacervation with GA and the O-CMC–GA coacervates displayed similar differential scanning calorimetry (DSC) patterns, thermogravity (TG) profiles, and porous microstructures, but differed markedly in their rheological properties. As the O-CMC DS increased, the elasticity of the coacervates raised accordingly. It was concluded that O-CMC–GA coacervates with desired viscoelasticity can be obtained by varying the DS of O-CMC. GRAPHICAL ABSTRACT: